(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To analysis of some factors affecting re-hospitalization due to narrow narrow stent again after iliac-femoral endovascular intervention in patients with chronic lower extremity artery disease due to atherosclerosis at the Institute of Cardiology in 2016-2017. Methods: The intervention study was performed on 64 limbs of 50 patients with chronic lower extremity artery disease who underwent endovascular intervention of the pelvis - femoral at the Cardiology Institute in 2016 - 2017. Result: There were 17.2% of lower extremities treated with narrow stent again in 6 months after the intervention. Factors that increased the risk of narrow stent again found in the study included an ankle-brachial index (ABI) less than 0.4; have multistage vascular lesions; have dyslipidemia; Using 2 or more stents and using stents longer than 16cm. Conclusion: The risk of narrow stent again after femoral endovascular intervention in patients with chronic atherosclerotic lower extremity artery disease is moderate, increased by the patient’s cardiovascular risk factors.